Characterization and Comparative Genomic Analysis of a Highly Colistin-Resistant Chryseobacterium gallinarum: a Rare, Uncommon Pathogen - Gaur, Mahendra; Dey, Suchanda; Sahu, Anshuman; Dixit, Sangita; Sarathbabu, S.; Zothanzama, John; Sahoo, Rajesh Kumar; Behera, Dibyajyoti Uttameswar; Monika,; Subudhi, Enketeswara (Frontiers in Cellular and Infection Microbiology, 2022)
For the first time, we describe the whole-genome of a yellow-pigmented, capsule-producing, pathogenic, colistin-resistant Chryseobacterium gallinarum strain MGC42 isolated from a UTI patient in India. VITEK 2 automated system initially identified this isolate as C. indologenes. However, 16S rRNA gene sequencing revealed MGC42 shared 99.67% sequence identity with C. gallinarum type strain DSM 27622. The draft genome of the strain MGC42 was 4,455,926 bp long with 37.08% GC content and was devoid of any plasmid. Antibiotic resistance, virulence and toxin genes were predicted by implementing a machine learning classifier. Potential homologs of 340 virulence genes, including hemolysin secretion protein D, metalloprotease, Catalase peroxidases and autotransporter adhesins, Type VI secretion system (T6SS) spike proteins and 27 toxin factors, including a novel toxin domain Ntox23 was identified in the genome. In addition, KEGG orthologues of 110 transporter proteins were predicted to agree with moderate efflux activity. Twelve antibiotic resistance genes, including two potentially novel putative β-lactamase genes sharing low similarity with known β-lactamase genes, were also identified in the genome of this strain. The strain MGC42 was resistant to several classes of antibiotics along with carbapenems and polymyxin. We identified mutations in the orthologs of pmrB (M384T) and lpxD (I66V) that might be responsible for colistin resistance. In addition, the MGC42 strain shared 683 core genes with other environmental and clinical strains of Chryseobacterium species. Our findings suggest that strain MGC42 is a multidrug-resistant, virulent pathogen. We recommend 16S rRNA gene sequencing to identify clinical specimens of Chryseobacterium species.